Efektivitas Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) Untuk Meningkatkan Pemahaman Konsep Matematis Dan Self efficacy Peserta Didik Kelas VIII SMP Negeri 2 Tebing Tinggi - Fitri Humairoh; Sri Lestari Manurung (FKIP Universitas Mataram, 2025)
This study aims to determine the effectiveness of the STAD cooperative learning model in improving mathematical concept understanding and self-efficacy among eighth-grade students at SMP Negeri 2 Tebing Tinggi. Using a Nonequivalent Pretest-Posttest Control Group Design, this study involved class VIII-5 as the experimental group and class VIII-6 as the control group, which were selected randomly. Based on the research conducted using the Mann-Whitney U test, the results showed that there was a difference in the average mathematical concept understanding of students between the experimental class using the STAD learning model and the control class using the direct learning model. This result was based on an Asymp Sig. (2-tailed) value of 0.002 < 0.05 and supported the research hypothesis that the use of the STAD model was effective in improving students' mathematical concept understanding. In terms of student self-efficacy, using the independent t-test, a Sig. (2-tailed) value of 0.650 > 0.05 was obtained, indicating that there was no difference in the average self-efficacy of students between the STAD learning model and the direct learning model.